2016
DOI: 10.1111/pin.12453
|View full text |Cite
|
Sign up to set email alerts
|

BAP1 immunohistochemistry and p16 FISH results in combination provide higher confidence in malignant pleural mesothelioma diagnosis: ROC analysis of the two tests

Abstract: Differentiation of malignant pleural mesothelioma (MPM) from benign mesothelial proliferation remains problematic. Loss of nuclear staining of BRCA1-associated protein 1 (BAP1; detected using immunohistochemistry (IHC)) and homozygous deletion (HD) of p16 (detected using fluorescence in situ hybridization (FISH)) are useful for differentiation of MPM from reactive mesothelial hyperplasia (RMH), but the correlation between BAP1 expression loss and p16 HD has not been fully described. We performed BAP1 IHC and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 38 publications
7
77
0
Order By: Relevance
“…Current recommendations for diagnosing MM suggest initial screening panels to include positive staining for at least 2 MM markers (such as calretinin, WT1 and CK5/6) and negative staining for at least 2 carcinoma markers (such as CEA, Leu M1, BerEP4 and TTF‐1) . More recent research has shown promising results using fluorescence in situ hybridization (FISH) analysis to detect homozygous deletion of p16 and immunohistochemistry to detect loss of nuclear staining of BRCA1‐associated protein 1 (BAP1), independently or in combination, for difficult cases of MM . This is especially useful in differentiating between malignant pleural mesothelioma and benign reactive mesothelial hyperplasia, which have cytologic and histologic similarities …”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations for diagnosing MM suggest initial screening panels to include positive staining for at least 2 MM markers (such as calretinin, WT1 and CK5/6) and negative staining for at least 2 carcinoma markers (such as CEA, Leu M1, BerEP4 and TTF‐1) . More recent research has shown promising results using fluorescence in situ hybridization (FISH) analysis to detect homozygous deletion of p16 and immunohistochemistry to detect loss of nuclear staining of BRCA1‐associated protein 1 (BAP1), independently or in combination, for difficult cases of MM . This is especially useful in differentiating between malignant pleural mesothelioma and benign reactive mesothelial hyperplasia, which have cytologic and histologic similarities …”
Section: Discussionmentioning
confidence: 99%
“…Clinically, these markers are quite useful because they have 100% specificity for differentiating malignant mesothelial proliferations from benign proliferations . Although the sensitivity of either of these markers is relatively insufficient, the combination approach of 9p21 FISH and BAP1 IHC has been found to enhance the sensitivity …”
Section: Introductionmentioning
confidence: 86%
“…So far, the BAP1 antibody has been tested primarily on biopsies. [13][14][15][16][17][18][19][20] Only a few studies have used BAP1…”
mentioning
confidence: 99%